Transferability of Laboratory Fracture Data to Safety Assessment of Postulated Defects in Critical NPP Components - Taylor, N.; Nilsson, K.F. (Проблемы прочности, 2004)
For strength evaluation of reactor pressure vessels, large-scale benchmark tests have been conducted on determination of fracture toughness of specimens with internal defects. The obtained results provide a good check on the transferability of data on standard materials to the assessment of real and postulated flaws in reactor pressure vessels. The Master Curve method makes it possible to get more reliable predictions of ductile-brittle transition, in comparison with approaches using KIc as function of RTndt.